Shape memory effect in nanocrystalline NiTi alloy processed by high-pressure torsion - Shahmir, Hamed; Nili-Ahmadabadi, Mahmoud; Huang, Yi; Myun Jung, Jai; Seop Kim, Hyoung; Langdon, Terence G. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2015)
A NiTi alloy was processed by high-pressure torsion for 10 turns followed by post-deformation annealing at 673K for various times. An anneal for 60min gave a nanocrystalline microstructure with a superior shape memory effect and an improvement of more than 40% over the initial state.